Targeting STAT3 in tumor-associated antigen-presenting cells as a strategy for kidney and bladder cancer immunotherapy - Alcantara, Marice B.; Tang, Wilson S.; Wang, Dongfang; Kaniowski, Damian; Kang, Elaine; Dizman, Nazli; Chehrazi-Raffle, Alexander; Meza, Luis; Zengin, Zeynep; Hall, Jeremy; Hsu, JoAnn; Egelston, Colt; et al. (Frontiers in Immunology, 2024)
Immune checkpoint blockade (ICB) improved clinical outcomes in renal and bladder cancer patients, but the response rates remain limited especially in metastatic disease. While STAT3 transcription factor is well-known master regulator of tumor immune evasion, little is known about the role of STAT3 in the resistance of renal or bladder cancers to immunotherapy. To better understand immune alterations associated with ICB resistance, we assessed blood biomarkers in renal cancer patients classified as responders or non-responders to first line nivolumab/ipilimumab immunotherapy. We observed that non-responders showed elevated levels of proinflammatory mediators, such as IL-1RA, IL-6, IL-8 and to lesser extent IL-10, which are associated with STAT3 activation and tumor immunosuppression. In addition, we found STAT3 activation primarily in circulating myeloid immune cells such as tolerogenic MDSCs. To assess whether STAT3 inhibition within these cell subsets can promote antitumor immune responses and/or enhance sensitivity to ICB in vivo, we used an original antisense oligonucleotide (ASO) strategy for myeloid-cell selective STAT3 knockdown (CpG-STAT3ASO). Our results in syngeneic models of renal and bladder cancers in mice demonstrated potent antitumor activity of CpG-STAT3ASO alone in contrast to PD1 blockade alone in both models. The CpG-STAT3ASO/anti-PD1 combination improved therapeutic efficacy especially against bladder tumors. Therapeutic efficacy correlated with activation of dendritic cells (DCs) and M1 macrophages in the tumor microenvironment, reduced percentages of regulatory T cells (Tregs) and the expansion of CD8 T cells in both tumor models. Our study underscores the potential of using myeloid-cell targeted CpG-STAT3 inhibitors for genitourinary cancer therapy to disrupt tolerogenic signaling, restore immune cell activity and sensitivity to immune checkpoint inhibitors and/or T cell-based immunotherapies.